Land and the Living Roots of Language: From Rights to Reconciliation - Fettes, Mark (Tusaaji: A Translation Review, 2017)
Included in the Calls to Action of Canada’s Truth and Reconciliation Commission are several Calls pertaining to Indigenous languages. However, the terms of Western discourse on rights, and on language itself, risk obscuring the fundamental connections between language and land that Indigenous Elders and scholars have insisted on. Drawing on a diverse literature, I argue that language is, indeed, bound up with the ways in which we inhabit the living world, and that genuine reconciliation requires rethinking language policy and management from this perspective.